2003
DOI: 10.1128/aac.47.9.2765-2769.2003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Azithromycin Administration for Trachoma Control on the Carriage of Antibiotic-Resistant Streptococcus pneumoniae

Abstract: Community distribution of azithromycin has an important role to play in trachoma control. Previous studies have suggested that this may increase the prevalence of macrolide-resistant Streptococcus pneumoniae. S. pneumoniae was isolated from children under 7 years of age in Rombo District, northern Tanzania, before and 2 and 6 months after community-wide administration of azithromycin. Overall carriage rates were 11, 12, and 7%, respectively. Only one macrolide-resistant isolate carrying the mef gene was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
56
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 23 publications
1
56
1
Order By: Relevance
“…The absence of azithromycin resistance at the first cross-sectional survey is consistent with previous studies carried out in Australia, Nepal and the United Republic of Tanzania, all of which showed that substantial azithromycin resistance did not develop following a single treatment dose in areas where the baseline prevalence of the carriage of resistant strains was low. [23][24][25] The prevalence of the carriage of azithromycin-resistant pneumococci rose to just over 1% at the second cross-sectional survey. However, at the third survey, there was no significant difference in prevalence between villages that received three annual MDA rounds and those that received one.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of azithromycin resistance at the first cross-sectional survey is consistent with previous studies carried out in Australia, Nepal and the United Republic of Tanzania, all of which showed that substantial azithromycin resistance did not develop following a single treatment dose in areas where the baseline prevalence of the carriage of resistant strains was low. [23][24][25] The prevalence of the carriage of azithromycin-resistant pneumococci rose to just over 1% at the second cross-sectional survey. However, at the third survey, there was no significant difference in prevalence between villages that received three annual MDA rounds and those that received one.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from studies conducted prior to 2001, which were conducted in populations with little exposure to azithromycin, describe temporary increases in the prevalence of antimicrobial drug-resistant Streptococcus pneumoniae carriage in treated children. 20,[25][26][27] No drug-resistant isolates were detected * Adjusted for effects of child's age < 2 years at enrollment, presence of a toilet in the household, and antibiotic treatment of acute lower respiratory illness during follow-up period. Standard errors corrected for clustering.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports on the implementation of the conjugate vaccine in different communities show that there is an increase in the carriage of serotypes that are not included in the vaccine (6,7). Additionally, serotype surveillance in developing countries and special populations, such as Aboriginal Australians, suggests that vaccine serotype coverage may be lower than for the United States and Europe, from which surveillance data were considered in vaccine formulations (2,4,25). Thus, there is a continuing need to study the epidemiology of S. pneumoniae as defined by capsular polysaccharide in monitoring the effect of conjugate vaccines and to aide in the development of new vaccine formulations for developing countries and special populations (12,13,16).…”
mentioning
confidence: 99%